The impact of tumor and lymph node characteristics on disease free survival in squamous cell vulvar cancer - Akdağ Cırık, Derya; Karalok, Alper; Üreyen, Işın; Türkmen, Osman; Taşcı, Tolga; Narin, Mehmet Ali; Köse, Mehmet Faruk; Boran, Nurettin; Turan, Taner; Tulunay, Gökhan (My University, 2016)
We aimed to determine the prognostic significance of tumor and lymph node (LN) characteristics on disease free survival (DFS) in patients who underwent surgery for squamous cell vulvar carcinoma. A total of 94 patients who underwent vulvar surgery and groin dissection were included. The impact of clinicopathologic variables such as age, body mass index, tumor size, tumor depth, total and metastatic lymph node number on DFS were assessed. The estimates of survival were determined with Kaplan-Meier and log rank analysis. In the univariate analysis; age, body mass index, tumor size, tumor location, total LN number, metastatic LN number and adjuvant therapy did not have impact on DFS. The median number of removed LNs was 21. Although removal of higher number of lymph nodes did not improved the DFS, patients who had <= 3 metastatic LNs had better 2-year DFS rate compared to those with >3 metastatic LNs (71.8% vs 40.0%; p= 0.042, respectively). In the multivariate analysis, both the depth of tumor invasion and LN involvement were the independent predictors of DFS. Additionally, in stage III disease, patients receiving adjuvant therapy had significantly less locoregional recurrence compared to those who did not receive. The presence of LN metastasis and increased tumor depth (> 3 mm) are poor prognostic factors for DFS in squamous cell vulvar cancer. Although the number of lymph nodes removed was not correlated with DFS, patients who had <= 3 metastatic LNs had better DFS compared to those with > 3 LNs.

Bu çalışmada, skuamöz hücreli vulva kanseri için cerrahi yapılan hastalarda tümör ve lenf nodu (LN) özelliklerinin hastalıksız sağkalıma (DFS) etkisini incelemek amaçlandı. Vulvar cerrahi ve lenf nodu diseksiyonu yapılan toplam 94 hasta çalışmaya dahil edildi. Yaş, vücut kitle indeksi, tümör boyutu, tümör derinliği, total ve metastatik LN sayısı gibi klinikopatolojik değişkenlerin DFS'ye etkisi araştırıldı. Sağkalım analizleri ise Kaplan-Meier ve log rank analizi ile yapıldı. Univaryant analizine göre, yaş, vücut kitle indeksi, tümör boyutu ve yeri, toplam LN sayısı, metastatik LN sayısı ve adjuvan tedavi DFS üzerine etkili bulunmadı. Ortalama olarak 21 tane LN çıkarıldı. Ortalamadan fazla lenf nodu çıkarılması DFS üzerine etkili olmasa da, 3 ve daha az metastatik LN çıkarılan hastalar, 3'den fazla metastatik LN çıkarılanlardan daha iyi 2-yıllık-DFS'ye sahip bulundu (sırasıyla, %71.8 ve %40.0; p= 0.042). Multivaryant analizde, hem tümör derinliği hem de LN tutulumu DFS'nin bağımsız prediktörleri idi. Ek olarak, evre III hastalıkta, adjuvan tedavi alan hastalar almayanlara göre daha az lokal (perineal ve kasık) nüksüne sahip idi. Lenf nodu metastazı ve artmış tümör derinliği (> 3 mm), skuamöz hücreli vulva kanseri için kötü prognostic faktörlerdir. Çıkarılan LN sayısı ile 2-yıllık-DFS korele olmasa da evre III hastalarda, 3 ve daha az metastatik LN çıkarılan hastalarda 3'den fazla LN çıkarılanlara göre daha iyi DFS izlenmektedir.
Skuamöz hücreli vulva kanserinde tümör ve lenf nodu özelliklerinin hastalıksız sağkalıma etkisi
Keywords: Vulvar Cancer; Lymph Node; Disease Free Survival; Recurrence; Vulva Kanseri; Lenf Nodu; Hastalıksız Sağkalım; Nüks